(untitled) (Research, Society and Development, 2025)
Indroduction: It is notable that, when it comes to the prevalence of psychosomatic illnesses associated with work-related factors, the healthcare field is prominently affected, particularly the nursing profession. The main precursors for the diagnosis of these psychopathologies are exhaustive work shifts, excessive patient contact, and exposure to the process of death and dying. The highlighted mental illnesses include burnout syndrome, anxiety, and depression. Objective: To investigate the impacts of the work environment on the mental health of nursing professionals, addressing the most prevalent psychosomatic disorders and their triggering factors. Materials and Methods: Systematic literature review through a survey of studies published between 2019–2023 in national and international journals, focusing on the predominance of mental illnesses among nursing professionals. Results: Among the analyzed studies, most have a cross-sectional design; two are descriptive-analytical, one uses a qualitative approach, and another presents a prospective design. The publication years range from 2022 to 2024, indicating the relevance and timeliness of investigations on this topic. Conclusion: The findings highlight that the work environment for nursing professionals is characterized by high emotional demands, overload, exhaustive work shifts, and adverse conditions—factors that contribute to mental suffering and directly impact their physical health. In this context, it becomes essential to implement prevention strategies and support programs aimed at nurses’ mental health, including improved working conditions, institutional policies for psychological support, and measures to promote well-being in the workplace.